2017
DOI: 10.1142/s0218216517400156
|View full text |Cite
|
Sign up to set email alerts
|

A survey on Heegaard Floer homology and concordance

Abstract: In this survey article, we discuss several different knot concordance invariants coming from the Heegaard Floer homology package of Ozsváth and Szabó. Along the way, we prove that if two knots are concordant, then their knot Floer complexes satisfy a certain type of stable equivalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 48 publications
0
73
0
Order By: Relevance
“…(1) picture each Z 2 -generator U m · x of C on the planar lattice Z × Z ⊂ R 2 in position (A(x) − m, −m) ∈ Z × Z, (2) label each Z 2 -generator U m · x of C with its Maslov grading M (x) − 2m ∈ Z, (3) connect two Z 2 -generators U n · x and U m · y with a directed arrow if in the differential of U n · x the coefficient of U m · y is non-zero. In [16] Ozsváth and Szabó show how to associate to a knot K ⊂ S 3 a knot type complex CF K ∞ (K) whose filtered chain homotopy type only depends on the isotopy class of K. For a concise introduction to the background material see [6].…”
Section: A Quick Review Of Knot Floer Homologymentioning
confidence: 99%
See 1 more Smart Citation
“…(1) picture each Z 2 -generator U m · x of C on the planar lattice Z × Z ⊂ R 2 in position (A(x) − m, −m) ∈ Z × Z, (2) label each Z 2 -generator U m · x of C with its Maslov grading M (x) − 2m ∈ Z, (3) connect two Z 2 -generators U n · x and U m · y with a directed arrow if in the differential of U n · x the coefficient of U m · y is non-zero. In [16] Ozsváth and Szabó show how to associate to a knot K ⊂ S 3 a knot type complex CF K ∞ (K) whose filtered chain homotopy type only depends on the isotopy class of K. For a concise introduction to the background material see [6].…”
Section: A Quick Review Of Knot Floer Homologymentioning
confidence: 99%
“…The quotient set CFK/ ∼ has a natural group structure: the sum is given by tensor product, the class of zero is the one represented by the Floer chain complex of the unknot CF K ∞ (U ), and the inverse of the class of a complex C is the one represented by its dual complex Hom(C, Z 2 [U, U −1 ]). Theorem 2.1 (Hom [6]). The map K → CF K ∞ (K) associating to a knot K ⊂ S 3 its knot Floer complex descends to a group homomorphism C → CFK/ ∼ .…”
Section: A Quick Review Of Knot Floer Homologymentioning
confidence: 99%
“…We believe that this link is not concordant to any link in S 3 , but we are not able to prove this at the moment. We also make a remark that the above question is a natural generalization of a theorem of Adam Levine [Lev16] (see also [HLL18]), where he proved that there exists a knot in a homology sphere which is not smoothly concordant to any knot in S 3 . As far as the authors knowledge, it is not known if such a statement is true for the topological category.…”
Section: Introductionmentioning
confidence: 91%
“…Two Heegaard Floer knot complexes are called stably equivalent if an acyclic complex can be added to each complex to make them filtered chain homotopy equivalent. In [6], Hom showed that if two knots are concordant, then their knot complexes are stably equivalent. The concordance invariants τ , ε, Υ, Υ 2 are all invariants of the stable equivalence class (see [5,6,8,11,12]).…”
Section: Introductionmentioning
confidence: 99%
“…6), x 2 = (1, 2) ⊗ (3, 3), x 3 = (2, 1) ⊗(1,6), and x 4 = (2, 1) ⊗(3,3).CFK ∞ (T (2, 5)) 0 ⊗ CFK ∞ (T (5, 6)) ∞ (T (2, 5)) 1 ⊗ CFK ∞ (T (5, 6)) The value of s for which each element at grading 1 is on the line L 4 5 ,s .Taking the boundaries, we get:∂(x 1 ) = ((0, 2) + (1, 1)) ⊗ (1, 6) = (0, 2) ⊗ (1, 6) + (1, 1) ⊗ (1, 6) = A + (1, 1) ⊗ (1, 6), ∂(x 2 ) = ((0, 2) + (1, 1)) ⊗ (3, 3) = (0, 2) ⊗ (3, 3) + (1, 1) ⊗ (3, 3) = B + (1, 1) ⊗ (3, 3), ∂(x 3 ) = ((2, 0) + (1, 1)) ⊗ (1, 6) = (2, 0) ⊗ (1, 6) + (1, 1) ⊗ (1, 6), ∂(x 4 ) = ((2, 0) + (1, 1)) ⊗ (3, 3) = (2, 0) ⊗ (3, 3) + (1, 1) ⊗ (3, 3).Notice that if Equation 5.1 is to hold, it must be that b 1 = b 2 = 1. Since∂(x 1 + x 2 ) = A + B + (1, 1) ⊗ (1, 6) + (1, 1) ⊗ (3, 3),we need b 3 = b 4 = 1 in order to counteract the extra contributions of x 1 and x 2 .…”
mentioning
confidence: 99%